Metaphors in the Short Story Paron Anthology by Poerwadhie Atmodhihardjo - Fieka Syarifatun Nabila; Siti Mulyani; Mohamad Makincoiri (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Metaphor is one of the many language styles used by authors. Research on the use of metaphors in short stories has been conducted with various short story anthologies. However, research on metaphors with the object of Javanese short stories has not been widely researched. The metaphors with the Javanese short story object are interesting to be researched, considering the many figurative language styles owned by Javanese literature. This study aims to describe the metaphors found in the Anthology of Paron Short Stories by Poerwadhie Atmodihardjo. The chapters to be discussed are: 1) form of metaphor lingual unit, 2) type of metaphor, and 3) function of metaphor in the Anthology of Paron Short Stories by Poerwadhie Atmodihardjo. This research is a descriptive research. The research data source is a collection of short stories with the title Anthology of Paron Short Stories. The data used are words, phrases, clauses, and sentences that use metaphors in the anthology of Paron short stories. The method of data collection used is listening and writing. How to analyze the data using descriptive techniques by explaining the form of lingual units, types and functions of metaphors used in the Paron Short Story Anthology. How to validate the data using the validity of theoretical triangulation, semantic validity and stability reality. The research results obtained are: 1) The word, phrase, clause, sentence metaphor, 2) Metaphor types are anthropomorphic, animalistic, abstracting, and synesthesia, 3) Metaphor functions are informational, expressive, directive, and phatic.